Field Marshal Sir Henry Wilson: A Political Soldier - Jeffery, Keith (Oxford University Press, 2006)
Henry Wilson was at the centre of affairs during the First World War and after, recording everything in his wildly indiscreet diary. Using a range of official and private sources, this is the first modern biography of this controversial and misunderstood figure.